Temporal changes in the probability of live birth among female survivors of childhood cancer: A population‐based Adult Life After Childhood Cancer in Scandinavia (ALiCCS) study in five nordic countries. Issue 20 (23rd July 2021) - Licht, Sofie de Fine; Rugbjerg, Kathrine; Andersen, Elisabeth W.; Nielsen, Thomas T.; Norsker, Filippa Nyboe; Kenborg, Line; Holmqvist, Anna S.; Madanat‐Harjuoja, Laura‐Maria; Tryggvadottir, Laufey; Stovall, Marilyn; Wesenberg, Finn; Hjorth, Lars; et al.
Abstract : BACKGROUND: During the past 4 decades, there has been a growing focus on preserving the fertility of patients with childhood cancer; however, no large studies have been conducted of live births across treatment decades during this period. Therefore, the authors estimated the potential birth deficit in female childhood cancer survivors and the probability of live births. METHODS: In total, 8886 women were identified in the 5 Nordic cancer registries in whom a childhood cancer had been diagnosed during 1954 through 2006. A population comparison cohort of 62, 903 women was randomly selected from the central population registries matched by age and country. All women were followed for live births recorded in medical birth registries. The cumulative probability and the risk ratio (RR) with 95% confidence intervals (CIs) of a live birth were calculated by maternal age across treatment decades. RESULTS: The probability of a live birth increased with treatment decade, and, at age 30 years, the rate for survivors most recently diagnosed was close to the rate among the general population (1954‐1969: RR, 0.65 [95% CI, 0.54‐0.78]; 1970s: RR, 0.67 [95% CI, 0.60‐0.74]; 1980s: RR, 0.69 [95% CI, 0.64‐0.74]; 1990s: RR, 0.91 [95% CI, 0.87‐0.95]; 2000s: RR, 0.94 [95% CI, 0.91‐0.97]). CONCLUSIONS: Female childhood cancer survivors had a lower probability of a live birth than women in the general population, although, in survivors diagnosed after 1989, the probability was close to that of the general population. Because the pattern of live births differs by cancer type, continuous efforts must be made to preserve fertility, counsel survivors, and refer them rapidly to fertility treatment if necessary. LAY SUMMARY: The purpose of this study was to compare the probability of giving birth to a liveborn child in female survivors of childhood cancer with that of women in the general population. Survivors of childhood cancer had a lower probability of live births than women in the general population, although survivors diagnosed after 1989 had a probability close to that of the general population. Continuing focus on how to preserve the potential for fertility among female patients with childhood cancer during treatment is important to increase their chances of having a child. Abstract : Female childhood cancer survivors have a lower probability of live birth than women in the general population. However, female survivors treated more recently in the 1990s and 2000s have a probability close to that of the female background population.